Dielectric absorption of s-polarized infrared light resonant to longitudinal optical phonon energy incident on lateral (0 0 0 1) GaN/Ti stripe structures. (12th February 2015) - Ishitani, Yoshihiro; Hatta, Keisuke; Morita, Ken; Ma, Bei
Abstract: The interaction of a semiconductor surface or interface and p-polarized infrared (IR) light has been investigated from the viewpoint of terahertz (THz) application. In this study the electric dipole absorption at the resonant energy to a longitudinal optical (LO) phonon of approximately 22 THz achieved using a lateral GaN/Ti stripe structure and s-polarized light, is clearer than the previously reported weak signal obtained using a film structure and p-polarized light. The previously proposed function of permittivity is validated by the analysis of Raman spectra in addition to IR analysis for the present sample structure. In the Raman spectra an additional peak is found at the higher-energy side of the LO phonon peak. The phonon-induced charges at the lateral GaN/Ti interface are greater than those at film interface, causing a greater dipole moment and stronger absorption in the vicinity of the LO phonon energy.